2023
DOI: 10.3389/fgene.2023.1080909
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of R2R3-MYB transcription factors in Boehmeria nivea (L.) gaudich revealed potential cadmium tolerance and anthocyanin biosynthesis genes

Abstract: Gene family, especially MYB as one of the largest transcription factor family in plants, the study of its subfunctional characteristics is a key step in the study of plant gene function. The sequencing of ramie genome provides a good opportunity to study the organization and evolutionary characters of the ramie MYB gene at the whole genome level. In this study, a total of 105 BnGR2R3-MYB genes were identified from ramie genome and subsequently grouped into 35 subfamilies according to phylogeny divergence and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…The gene duplication of PnTLPs in P. notoginseng genome was performed by MCscanX with the default parameters, and circus was used to locate all the PnTLP genes on the P. notoginseng chromosome by Tbtools version 1.120 (Du, Zhang, et al, 2022). The syntenic relationships between the PnTLP genes and TLP genes from A. thaliana and O. sativa were obtained also using McscanX and both results visualized in Tbtools (Feng, Abubakar, et al, 2023).…”
Section: Gene Duplication and Collinearity Analysis Of Pntlp Genesmentioning
confidence: 99%
“…The gene duplication of PnTLPs in P. notoginseng genome was performed by MCscanX with the default parameters, and circus was used to locate all the PnTLP genes on the P. notoginseng chromosome by Tbtools version 1.120 (Du, Zhang, et al, 2022). The syntenic relationships between the PnTLP genes and TLP genes from A. thaliana and O. sativa were obtained also using McscanX and both results visualized in Tbtools (Feng, Abubakar, et al, 2023).…”
Section: Gene Duplication and Collinearity Analysis Of Pntlp Genesmentioning
confidence: 99%
“…The potential involvement of the ramie WOX genes in adventitious root formation was investigated using quantitative real-time PCR and transcriptomic analysis of the ramie tissues grown using stem cuttings according to previous reports [43,44]. The transcriptome analysis of tissue-specific expression of the WOX genes was performed using four different ramie tissues (bud, leaf, stem, and root) sequenced by our laboratory, which was previously reported by Chen et al [3].…”
Section: Expression Patterns Analysismentioning
confidence: 99%
“…Previous studies have revealed that ramie crop has robust tolerance to Cd stress and can accumulate Cd ions from soil; hence, the use of ramie to prevent the Cd contamination of agricultural soils is of practical significance [27][28][29]. More significantly, ramie can accumulate a comparatively large number of heavy metals in its above-ground portion [30]. Ramie is a relatively tolerant crop against heavy metals stress, especially Cd stress, as it absorbs Cd from heavy metals-contaminated soils [27,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…More significantly, ramie can accumulate a comparatively large number of heavy metals in its above-ground portion [30]. Ramie is a relatively tolerant crop against heavy metals stress, especially Cd stress, as it absorbs Cd from heavy metals-contaminated soils [27,30,31]. An earlier study showed that ramie has a certain degree of tolerance to soil Cd stress at a concentration of ≤20 mg/kg [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation